Complicaciones y adherencia al tratamiento en pacientes hipertensos atendidos en el Centro de Salud Héroes del Cenepa de Loja - Luna Jiménez, Cristian Xavier (2022)
The arterial hypertension is one of the most common illnesses that affects human health and represents the mayor risk of cardiovascular mortality. The therapeutic adherence is defined like the accomplishment of treatment is vital to prevent the persistence of complications that can be cardiovascular, neurological and renal. This investigation has the purpose to know the risk factors for the therapeutic adherence in hypertensive patients according to their gender and age group, identify therapeutic adherence and hypertensive complications, and then establish the relation between both. This study was descriptive, cohort transversal retrospective, with 137 patients treated in the health center “Héroes del Cenepa”, it was applied “Test de Bonilla y Reales” searching the risks factors of therapeutic adherence, and the “Test de Morisky – Green” to value the treatment accomplishment. The results obtained showed that the predominant risk factors in men and women were: absence of communication with the doctor representing the 17,14% (n=6) and the feeding and physical activity in 45,9% (n=39), respectively. In the therapeutic adherency male gender is the less adherent with 24,2% (n=8). The neurologic complications were the most frequent with 62,8% (n=27). As conclusion the main risk factors for therapeutic adherence are “change in diet and physical activity” between with “absence of communication with the doctor”; the male gender was the less adherent and the main complications were neurologic. It does not exist relation between therapeutic adherency and the presence of complications